Nesting ecology of stingless bees (Hymenoptera, Meliponina) in urban areas: the importance of afforestation (Bioscience Journal, 2013)
Studies on nesting ecology have proven to be extremely important for stingless bees conservation. This kind of study is scarce in urban landscapes. Our study aimed to analyze the abundance, density, diversity, spatial distribution and nesting habits of species belonging to the Meliponina subtribe in an urban area of the Uberlândia municipality, Minas Gerais state. We checked potential nesting sites by searching for nests from October 2009 until April 2010. We collected six worker bees from each detected nest to identify species, and estimated diversity and analyzed the spatial distribution pattern of the nests using the Shannon-Wiener and Nearest Neighbor index, respectively. We found fifty nests belonging to seven species, with Nannotrigona testaceicornis being the most abundant species (44%). The density of nests was 2.17 nests/ha, the Shannon-Wiener diversity index was H'=1.58 and the clumped distribution was the detected dispersal pattern. The height of the nests in relation to the ground varied from 0 to 12 m: Trigona spinipes had the highest nests and the highest variation for this parameter. Hollow trees were the preferred substrate occupied by the observed bees species (70%): Caesalpinia peltophoroides was the preferred plant species for nesting. Our results suggested that urban landscapes can sustain a high diversity of stingless bees, and maintaining trees species and urban forestry projects are important tools for the conservation of this group of animals. This type of study provides relevant information to the development of management and conservation plans for Meliponina species.